Electrical Power Exchange in GMS and Its Influence on Power Systems in Vietnam and Thailand - Linh, T.T.D.; Mithulananthan, N.; Lomi, A.; Atputharajah, A.; Yome, A.S. (Second IEEE International Conference on Sustainable Energy Technologies, 2010)
The paper aims to identify the development of power interconnection network in the Greater Mekong Sub-region (GMS) which is a part of the major energy infrastructure mandated by ASEAN delegates in 1997. An overview of power systems in the region is introduced. The combined load curve for Vietnam and Thailand are formed to show the benefit of power grid interconnection of GMS. The paper also concentrates on simulation, analysis and evaluation of power transfer in 500kV and 220kV interconnection transmission lines in GMS for the planning horizon of 2010-2020. Reliability and environmental benefits of the interconnection are discussed due to interconnection. Based on the simulation results few recommendations are given.